2015
DOI: 10.1177/1938640015599036
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Amputation and Mortality Rates in the Reconstructed Diabetic Charcot Foot and Ankle With External Fixation

Abstract: Prognostic, Level III: Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
1
2
1
Order By: Relevance
“…showed a major amputation rate of 6.2% in their retrospective study of 292 persons, comparable with the amputation rate of Wirth et al 6 . and Ramanujam et al 14 . Because of the comparatively large number (31%) of dropouts and short follow‐up (24 months) in Illgner’s study, 9 an incorrectly low amputation rate can be assumed here.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…showed a major amputation rate of 6.2% in their retrospective study of 292 persons, comparable with the amputation rate of Wirth et al 6 . and Ramanujam et al 14 . Because of the comparatively large number (31%) of dropouts and short follow‐up (24 months) in Illgner’s study, 9 an incorrectly low amputation rate can be assumed here.…”
Section: Discussionsupporting
confidence: 83%
“…Because of the comparatively large number (31%) of dropouts and short follow‐up (24 months) in Illgner’s study, 9 an incorrectly low amputation rate can be assumed here. In their study of 116 people, Ramanujam et al 14 . had a larger proportion of those without ulcer (48%) compared with our study (42%).…”
Section: Discussioncontrasting
confidence: 67%
“…27 Two other series that were not included in this review reported even more impressive results, with LEA rates of 0% 28 and 6%. 20 Other studies demonstrate major LEA rates ranging from 11% to 15%. 25,31 These differences can partially be explained by stage at presentation, the presence or absence of a Charcot-related foot wound, the presence of absence of infection, and the technology available.…”
Section: Discussionmentioning
confidence: 94%
“…Pinzur et al [ 41 ] reported 3 amputations (4.2%) in a cohort of 71 patients who underwent single-stage resection of infection and correction of deformity with a ring fixateur. Ramanujam et al [ 42 ] reported one lower extremity amputation (3.7%) in 27 patients with diabetic CN and osteomyelitis who underwent surgical reconstruction using circular external fixation.…”
Section: Discussionmentioning
confidence: 99%